The Economics of Autocracy and Majority Rule - Olson, Mancur; McGuire, Martin C. (Journal of Economic Literature, 2010)
Productive public good investment allocations, and group discriminatory redistributions are conflicting resource use options between which every government must choose irrespective of its political make up. This paper is the first to derive an incisive explanation of how governments combine political and economic calculation to balance these competing choices. Realistic societies can be analyzed as a mixture of two polar cases — idealized, utopian, consensual democracy and perfect autocracy. Thus, in making the choice between social investment and redistributive taxation every government behaves somewhat like an pure democracy and somewhat like a selfish dictatorship.